Using weather data to support smallholder agriculture in Africa - Quak, Evert-Jan (Technical Centre for Agricultural and Rural Cooperation, 2018)
Providing added value services for smallholders using open weather data in developing countries is challenging. Therefore, on 21 and 22 November 2017 practitioners, policy-makers and academics gathered in The Hague, the Netherlands, to explore in two workshops the practical and strategic challenges they face to work with open weather data and how to address them.